(untitled) (Ibrahim Cardiac Medical Journal, 2019)
The growth of communication technology in the last two decades has given the world a new look.With the blessings of digital technology, we can now communicate to any parts of the world with just a touch over the screen of our smart phone. Mobile phone hasnow become an indispensable part of our life.But, biological effects of radio-frequency electromagnetic fields (EMF) transmitted by mobile phones are still a matter of public and scientific debate. Countries accross the world are now getting concerned about the impact of mobiles on human health and environment.Radiofrequency waves generated from mobile phones cause potential public health problems. Short-term effects like changes in sleep, heart rate, and blood pressure, and long-term effects like carcinoma (particularly glioma) are well-documented. International Agency for Research on Cancer (IARC) published cancer risks from Radiofrequency(RF) radiation. Human epidemiological studies gave evidence of increased risk for glioma and acoustic neuroma. Further epidemiological, animal and mechanistic studies have strengthened the association. Besides, the carcinogenic effect of non-ionizing radiation emitted from cordless digital devices, numerous health effects have already been claimed to occur. Faced with this context, scientific community and legislative bodies are raising voice for the reduction of RF-EMF exposure to the safe limit for human health and environment. The RF exposure restriction guideline used by many agencies was established in 1998 by the International Commission on Non-Ionizing Radiation Protection (ICNIRP) and was based only on established short-term thermal (heating) effects from RF radiation neglecting non-thermal biological effects. The present study is, therefore, intended to review the literatures relating mobile phone and Wi-fito human health in order to make the scientific community updated on the association between mobile phone use and human health. Ibrahim Card Med J 2018; 8 (1&2): 53-65